Erythropoietin reduces myocardial infarction and left ventricular functional decline after coronary artery ligation in rats - Moon, Chanil (National Academy of Sciences, 2003)
Erythropoietin (EPO), well known for its role in stimulation of erythropoiesis, has recently been shown to have a dramatic neuroprotective effect in animal models of cerebral ischemia, mechanical trauma of the nervous system, and excitotoxins, mainly by reducing apoptosis. We studied the effect of single systemic administration of recombinant human EPO (rhEPO) on left ventricular (LV) size and function in rats during 8 weeks after the induction of a myocardial infarction (MI) by permanent ligation of the left descending coronary artery. We found that an i.p. injection of 3,000 units/kg of rhEPO immediately after the coronary artery ligation resulted, 24 h later, in a 50% reduction of apoptosis in the myocardial area at risk. Eight weeks after the induction of MI, rats treated with rhEPO had an infarct size 15–25% of the size of that in untreated animals. The reduction in myocardial damage was accompanied by reductions in LV size and functional decline as measured by repeated echocardiography. Thus, a single dose of rhEPO administered around the time of acute, sustained coronary insufficiency merits consideration with respect to its therapeutic potential to limit the extent of resultant MI and contractile dysfunction.